1352 Survey of Management of Neonatal Hyperglycaemia in Level 3 Neonatal Units in UK. (October 2012) - Gupta, A; Lakshmanan, A; Harikumar, C; Janakiraman, S
Abstract : Introduction: and aim: Hyperglycaemia in preterm babies is a common problem. It is known to be associated with an increased risk of morbidity and mortality, especially in extreme preterm babies. Despite this, there is little established consensus of management. Nonetheless, practice is improving as the neonatal units develop local guidelines on the basis of the limited available research. Currently we don't know the specifics of the prevailing practice, and this is the first needed step in order to carry out any substantial further research. We carried out the survey to study the prevailing practice in level 3/tertiary units in the United Kingdom. Methods: We collated a list of level 3 units from the British Association of Perinatal Medicine (BAPM) website. We sent an online questionnaire to the Neonatal Consultant. We followed up with a phone call to get more responses. Results: We received responses from 51 units (81%). It showed that the 80% of units either follow local or regional guidelines and the majority (78.4%) now use gas machine for measuring blood glucose. We found there is quite a variation in definition of hyperglycaemia, modalities of management, insulin regimen and the endpoint of treatment. Conclusions: Management of neonatal hyperglycaemia is very unit dependant. We agree with other experts that large randomised trials in hyperglycaemic VLBW neonates that are powered on clinical outcomes are needed to determine whether and how the hyperglycaemia should be treated.